Cigarette Smoking Is Associated with a Lower Concentration of CD105+ Bone Marrow Progenitor Cells. (9th August 2015) - Beyth, Shaul; Mosheiff, Rami; Safran, Ori; Daskal, Anat; Liebergall, Meir
Abstract : Cigarette smoking is associated with musculoskeletal degenerative disorders, delayed fracture healing, and nonunion. Bone marrow progenitor cells (BMPCs), known to express CD105, are important in local trophic and immunomodulatory activity and central to musculoskeletal healing/regeneration. We hypothesized that smoking is associated with lower levels of BMPC. Iliac bone marrow samples were collected from individuals aged 18–65 years during the first steps of pelvic surgery, under IRB approval with informed consent. Patients with active infectious or neoplastic disease, a history of cytotoxic or radiation therapy, primary or secondary metabolic bone disease, or bone marrow dysfunction were excluded. Separation process purity and the number of BMPCs recovered were assessed with FACS. BMPC populations in self-reported smokers and nonsmokers were compared using the two-tailed t -test. 13 smokers and 13 nonsmokers of comparable age and gender were included. The average concentration of BMPCs was 3.52 × 10 5 /mL ± 2.45 × 10 5 /mL for nonsmokers versus 1.31 × 10 5 /mL ± 1.61 × 10 5 /mL for smokers ( t = 3.2, P = 0.004 ) . This suggests that cigarette smoking is linked to a significant decrease in the concentration of BMPCs, which may contribute to the reduced regenerative capacity of smokers, with implications for musculoskeletal maintenance and repair.